Periocular capillary hemangioma: management practices in recent years - Hernandez JA (Dove Medical Press, 2013)
Jo Anne Hernandez,1,3,4 Audrey Chia,2 Boon Long Quah,1,2 Lay Leng Seah1,2 1Department of Ophthalmology, Kandang Kerbau Women's and Children's Hospital, Singapore; 2Singapore National Eye Centre, Singapore; 3National Healthcare Group Eye Institute, Tan Tock Seng Hospital, Singapore; 4Department of Ophthalmology, Cardinal Santos Medical Center, San Juan, Manila, Philippines Purpose: To present a case series on the management options for capillary hemangiomas involving the eyelid and orbit. Methods: This is a retrospective chart review of clinically diagnosed capillary hemangioma cases involving the periocular region treated at two local eye institutions. The patients' demographics and clinical presentation – including visual acuity, refractive error, periorbital and orbital examinations, and ultrasound and magnetic resonance imaging findings – were reviewed. The clinical progression, modalities of treatment, and treatment outcomes were studied. Results: Sixteen cases of capillary hemangiomas involving the eyelid and orbit were studied. The mean age at consultation was 9.6 months (range: 1 month–72 months). The majority were females (75%), with 50% presenting as upper-eyelid hemangiomas and the remaining as lower-eyelid (38%) and glabellar (12%) lesions. Combined superficial and deep involvement was common (64%). Cases whose lesions were located at the upper eyelid or superior orbit led to amblyopia (25%). Fifty-six percent of cases (9/16) were managed conservatively, and 44% (7/16) underwent treatment with either single-agent (n = 4) or combined treatments (n = 3). Conclusion: Close monitoring of visual development and prompt institution of amblyopia therapy for children with periocular capillary hemangiomas generally preserve vision. Extensive lesions that affect the visual axis require local and systemic treatments, alone or in combination, in order to reduce the size and impact of lesions on the eyeball, to reduce induced refractive error and visual occlusion, and to prevent the development of amblyopia, in order to achieve good visual outcomes. Keywords: vascular, vascular malformation, bleomycin, propranolol, prednisolone, amblyopia